Pendampingan Ibu Hamil dalam Melaksanakan Senam Hamil Sebagai Upaya Meningkatkan Kesehatan Ibu di Desa Oelnasi Kabupaten Kupang Tahun 2023 - Matje Meriaty Huru; Maria Florentina Nining Kosad; Agustina Abuk Seran; Kamilus Mamoh (Rena Cipta Mandiri, 2025)
The health of pregnant women is one of the important indicators in determining the degree of public health, because it is directly related to maternal mortality rates (AKI) and infant mortality rates (AKB). One of the promotive approaches that can be done to improve maternal health during pregnancy is through pregnancy exercises, which is a form of light physical exercise that aims to strengthen muscles, facilitate breathing, and prepare mothers for the delivery process. Pregnant women who regularly participate in gymnastics experience improved physical condition, reduced stress, and are more mentally prepared to face childbirth than those who do not. The purpose of this activity is to help pregnant women engage in pregnancy exercises as a means to increase their knowledge and promote maternal health. The method used is through counseling. The partners in this activity are all pregnant women in Oelnasi Village, totaling 10 people. Evaluation of knowledge using pre-test and post-test questionnaires. The results of the assessment showed that the average pre-test score was 69.3 (SD=6.98) and the average post-test score was 89.6 (SD=6.79). The results of the statistical test showed that there was a significant increase in the knowledge of pregnant women after the provision of educational materials about pregnancy exercises (p = 0.000; α < 0.05).